Quality or Quantity: Completion Rewards and Formative Assessments in Flipped Instruction Classes - Kurt Schmitz (International Journal for the Scholarship of Teaching and Learning, 2019)
Flipped instruction shifts the burden for engaging course content to the students. Moving these activities outside the classroom creates motivational challenges. This study investigates the role of formative assessments and completion rewards. Definitions are provided for flipped instruction and formative assessments. A classification of reward scores is offered to guide data collection in two field experiments. The study seeks to provide an empirical basis to guide use of completion rewards for flipped instruction classes. This study finds that completion rewards can increase quantity of formative assessment engagement. However, this change in quantity does not improve exam scores. The data suggests completion rewards may undermine the quality of engagement.